ANALISIS VARIASI WAKTU PENGERINGAN DAN KECEPATAN UDARA PANAS TERHADAP KINERJA PADA MESIN PENGERING KERUPUK RUMPUT LAUT DENGAN SISTEM HYBRID - Muhammad Yaz Rasyid; Mietra Anggara; Aldrin Aldrin; Fadhli Dzil Ikram (Program Studi Teknik Mesin Fakultas Rekayasa Sistem Universitas Teknologi Sumbawa, 2026)
Seaweed is a strategic commodity for aquaculture which has benefits as a food ingredient. The seaweed that is popular with the public is seaweed crackers. Technological developments have developed drying using the fluidization principle. The aim of the research was to determine variations in air speed and variations in drying time on drying rate, water content, drying efficiency. 180 minute test, the highest drying rate value was at 1 m/s, namely 2.03 g/minute, the lowest drying rate value was at 2 m/s, namely 2 g/minute, in the 360 ??minute test, the highest drying rate value occurred at 1 m/s. s, namely 1.10 g/minute, the lowest value of drying rate at 1.5 m/s, namely 1.08 g/minute. Drying 180 minutes with varying air speeds of 1 m/s, 1.5 m/s, 2 m/s, water content is 7.74%, 8.08%, 8.8%. Drying 360 minutes with varying air speeds of 1 m/s, 1.5 m/s, 2 m/s, water content is 1.62%, 2.34%, 2.04%, all water content meets SNI. Drying 180 minutes with varying air speeds of 1 m/s, 1.5 m/s, 2 m/s, drying efficiency is 6.67%, 5.71%, 6.26%. 360 minutes drying with varying air speeds of 1 m/s, 1.5 m/s, 2 m/s, drying efficiency of 3.82%, 3.59%, 3.58%.